Neoadjuvant Therapy in Early Breast Cancer: Treatment Considerations and Common Debates in Practice. Issue 10 (October 2017) - Cain, H.; Macpherson, I.R.; Beresford, M.; Pinder, S.E.; Pong, J.; Dixon, J.M.
Abstract: Neoadjuvant treatment offers a number of benefits for patients with early breast cancer, and is an important option for consideration by multidisciplinary teams. Despite literature showing its efficacy, the use of neoadjuvant therapy varies widely. Here we discuss the clinical evidence supporting the use of neoadjuvant therapy in early stage breast cancer, including patient selection, monitoring response, surgery and radiotherapy considerations, with the aim of assisting multidisciplinary teams to determine patient suitability for neoadjuvant treatment. Highlights: Neoadjuvant treatment is an increasingly important part of early breast cancer management. Multidisciplinary teams play a key role in the decision process for neoadjuvant treatment. Neoadjuvant therapy practice still varies widely. Expert discussion on current evidence to support neoadjuvant treatment decisions for patients.